Perbandingan Daya Terima Dan Karakteristik Cookies Tepung Hati Ayam Kampung Dan Tepung Pisang Kepok - Thalia, Raden Rara Lavidhea Aldefinna; Rohmansyah, Ryan (Poltekkes Kemenkes Yogyakarta, 2025)
Background: Native chicken liver flour is a food ingredient obtained from Native chicken liver.Native chicken liver is one of the food ingredients that contains high iron. The utilization of chickenliver flour is done in the form of cookies, which is a snack that is often consumed by the communityand can be a side dish. Objective: Analyzing the comparison of the acceptability of cookies on the characteristics of color, taste, aroma, and texture of 4 formulas. Methods: This research used a complete randomized design (CRD) type of experimental research with 1 control and 4 (four) treatments and data processing using ANOVA test and Duncan's further test using Statistical Program for Social Science (SPSS). Results: The results of hedonic test analysis using ANOVA showed that F0, F1, F2, F3 there were significant differences in color, taste, aroma, and texture significance 0.000 (p < 0.05). While the results of the organoleptic quality test analysis using ANOVA show that F0, F1, F2, F3 show that there are significant differences in color, taste, and aroma with a significance of 0.000 (p < 0.05). However, there is no significant difference in texture significance 0.358 (p>0.05). Conclusion: There is a comparison of the acceptability and characteristics of cookies with the addition of Kampong chicken liver flour and kepok banana flour in each treatment. F3 became the selected formula because it obtained the highest value in the parameters of color, taste, aroma, and texture